2011
DOI: 10.1542/peds.2010-0533
|View full text |Cite|
|
Sign up to set email alerts
|

Vitamin D Status in Abused and Nonabused Children Younger Than 2 Years Old With Fractures

Abstract: Vitamin D insufficiency was common in young children with fractures but was not more common than in previously studied healthy children. Vitamin D insufficiency was not associated with multiple fractures or diagnosis of child abuse. Nonaccidental trauma remains the most common cause of multiple fractures in young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…In addition, serum 25OHD levels are similar in infants with accidental and nonaccidental injuries [53] . Thus, simple vitamin D deficiency, that is vitamin D deficiency without biochemical or radiological signs of rickets, has not been associated with an increased fracture risk in infants and children.…”
Section: 2 Evidencementioning
confidence: 92%
“…In addition, serum 25OHD levels are similar in infants with accidental and nonaccidental injuries [53] . Thus, simple vitamin D deficiency, that is vitamin D deficiency without biochemical or radiological signs of rickets, has not been associated with an increased fracture risk in infants and children.…”
Section: 2 Evidencementioning
confidence: 92%
“…A physiologic PTH level in infants with fractures has not been identified, but a study showed that children with rib fractures are more likely to have elevated PTH than children with fractures in other bones, and the younger the child, the more elevated the PTH. 9 Our patient also had a 25-hydroxyvitamin D level that was in the insufficient range. Although vitamin D insufficiency has been proposed as a factor predisposing children to fractures and potentially causing erroneous diagnoses of abuse, the 1 study of vitamin D levels in infants and children with fractures showed no increased fracture risk with vitamin D levels in the insufficient range (20Y30 ng/mL).…”
Section: Discussionmentioning
confidence: 60%
“…In a recent review of children with vitamin D deficiency, the rachitic changes and demineralization were uncommon, and the fracture risk was low (Perez-Rossello, Feldman, Kleinman, Connolly, Fair, Myers, & Gordon, 2012). In a separate study of vitamin D levels and fractures, the authors concluded that the vitamin D insufficiency was not associated with multiple fractures and diagnosis of child abuse, and nonaccidental trauma remains the most common cause of multiple fractures in young children (Schilling, Wood, Levine, Langdon, & Christian, 2011).…”
Section: Differential Diagnosismentioning
confidence: 99%